Eagles enter rotor‐swept zones of wind turbines at rates that vary per turbine. Issue 16 (21st July 2021) - McClure, Christopher J. W.; Rolek, Brian W.; Braham, Melissa A.; Miller, Tricia A.; Duerr, Adam E.; McCabe, Jennifer D.; Dunn, Leah; Katzner, Todd E.
Abstract: There is increasing pressure on wind energy facilities to manage or mitigate for wildlife collisions. However, little information exists regarding spatial and temporal variation in collision rates, meaning that mitigation is most often a blanket prescription. To address this knowledge gap, we evaluated variation among turbines and months in an aspect of collision risk—probability of entry by an eagle into a rotor‐swept zone (hereafter, "probability of entry"). We examined 10, 222 eagle flight paths identified and recorded by an automated bird monitoring system at a wind energy facility in Wyoming, USA. Probabilities of entry per turbine–month combination were 4.03 times greater in some months than others, ranging 0.15 to 0.62. The overall probability of entry for the riskiest turbine (i.e., the one with the greatest probability of entry) was 2.39 times greater than the least‐risky turbine. Our methodology describes large variation across turbines and months in the probability of entry. If subsequently combined with information on other sources of variation (i.e., weather, topography), this approach can identify risky versus safe situations for eagles under which cost of management, curtailment prescriptions, and collision risk can be simultaneously minimized. Abstract : Rates that eagles entered rotor‐swept zones of wind turbines varied by turbine across a wind farm in Wyoming, USA. Such variation demonstrates that curtailment criteria should vary per turbine and season.